Children with cochlear implants in infancy: predictors of early vocabulary. Issue 4 (23rd March 2018) - Bavin, Edith L.; Sarant, Julia; Leigh, Greg; Prendergast, Luke; Busby, Peter; Peterson, Candida
Abstract: Background: Language outcomes for children with cochlear implants (CIs) vary widely, even for those implanted before 2 years of age. Identifying the main influencing factors that account for some of the variability is important in order to provide information to guide appropriate clinical and intervention services for young children with CIs. However, there is limited research focusing on the predictors of early vocabulary development for children implanted in infancy. Aims: To identify significant predictors of vocabulary (12–15 months post‐implant) for a sample of 33 children with CIs, the majority implanted between 6 and 10 months of age, drawing on predictors of vocabulary reported for children with normal hearing. Of particular interest was the impact of pre‐implant development and use of gestures. Methods & Procedures: Children with severe to profound hearing loss, and no other known disabilities, were recruited from CI clinics in Australia before receiving their CIs. Subscales from the Bayley Scales‐III (receptive and expressive communication, gross and fine motor, and cognition) were used to assess their development at that time. Using the Macarthur–Bates Communicative Development Inventory (Words and Gestures) we documented the children's (1) use of gestures at six data‐collection times 3 months apart; and (2) vocabulary at the last three time points. Time since implant and time to consistent use of the CIs were also included as potential predictors. Data were analysed using generalized linear models, assuming a negative binomial response with a log‐link function. Stepwise variables selection was followed to retain a smaller number of the covariates. Outcomes & Results: A year after implantation, the significant predictors identified for vocabulary were pre‐implant receptive communication and early gesture use. Together with fine motor and cognitive skills, these two variables were also significant predictors of vocabulary 3 months later. With maternal education entered into the models, higher vocabulary scores were significantly associated with higher maternal education 12 months post‐implantation, but not 15 months. Conclusions & Implications: Pre‐implant abilities are important in explaining some variability in the early vocabulary of infants with CIs, together with their use of early gestures post‐implantation. That is, having a non‐verbal means to express a concept can assist in their development of oral vocabulary. Identifying strategies to help develop fine motor skills for infants with CIs, and encouraging their use of gestures to communicate their needs/intentions, are likely to be of benefit.